Isothermal oxidation behavior of YAl3C3 at 900–1300 °C in air. Issue 8 (July 2020) - Zhao, Guorui; Li, Yueming; Chen, Jixin; Li, Jialin; Li, Meishuan
Abstract: The isothermal oxidation behavior of YAl3 C3 in air has been investigated at 900−1300 °C for 20 h. At 900 and 1000 °C, the oxidation kinetic curves of YAl3 C3 obey parabolic rate law. The oxide scales have a bilayer structure. The outer layer is composed of YAG and amorphous Al2 O3, and the inner layer is a carbon-rich layer. The oxidation kinetic curves of YAl3 C3 obey linear law above 1100 °C. The oxide scales have a monolayer structure composed of Al2 O3 and YAG. The crystallization transformation of amorphous Al2 O3 causes the oxidation kinetic curve changing from a parabolic to a straight line.